Análise cognitiva e perceptivo-motora de idosos praticantes e não praticantes de exercício físico - Macedo, Thuane Lopes (2017)
The process aging is very complex and concern on various limitations of the individual. Over the years occurs physiological decline as can change cognitive and motor performance, decreasing your functional capacity and interfering on your quality of life and autonomy. There is evidence that aerobic exercise can reduce this damage, but these relationships are not clear. The objective of this study was to analyze and compare the cognitive and perceptual-motor profile in active and sedentary aged. Were selected elderly practicing gymnastics (GG, n=29) and not practicing physical exercises (GC, n=30) the ages of 60 and 79 years. We evaluated the simple reaction time, capacity attention and concentration and peripheral perception of the elderly through the Vienna Test System®. Moreover, a survey was made of socioeconomic variables that could affect cognitive functions. To test the normality of the data was used the Shapiro Wilk Test. The association between physical activity and socioeconomic variables was verified through the Chi-Square Test and Fisher Exact Test. To compare of differences between groups we used the Mann Whitney U-test for variables non-parametric distribution, and Student T-test for independent samples for other variables. All analyses were done using the statistical program SPSS® (20.0 version for Windows). As a result the article entitled “Analysis of the cognitive aspects of elderly people without cognitive impairment due to the practice of regular physical exercises and associated factors”. There were no significant differences in the performance of the groups, except in the capacity of attention and concentration on GC presented best performance (p=0.01). Factors as level of education (p=0.02), income (p=0.001) and practice regular of cognitive activity (p=0.06) can explain the best performance of GC. Concluded that isn’t evidence that the regular practice of physical exercise, by itself, can generate some cognitive benefit in healthy elderly when compared to elderly who did not practice regular physical exercise. It is understood that other aspects can influence positively the cognitive performance of elderly overlapping to the practice of physical exercise. Larger studies that examine other possible variables of cognition managers are needed to confirm if the aerobic training improves or not cognition of the elderly. Moreover new studies that compare the effectiveness of various sports can suggest if there is a more suitable for cognitive.